2007
DOI: 10.1089/aid.2006.0155
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic Resistance to Antiretroviral Drugs in Patients Infected with Several HIV Type 1 Genetic Forms in Cuba

Abstract: The main objective of this study is to evaluate the prevalence of resistance-associated mutations to reverse transcriptase (RT) and protease (PR) inhibitors (I) 2 years after the introduction of antiretroviral treatment in Cuba, analyzing the mutations corresponding to different HIV-1 genetic forms circulating in Cuba. A total of 425 plasma samples were collected in 2003, corresponding to 175 (41.2%) subtype B and 250 (58.8%) non-B genetic forms, including 56 (22.4 %) non-B subtypes, 112 (44.8%) circulating re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1
7

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 27 publications
0
14
1
7
Order By: Relevance
“…3 In another study done with samples collected mostly in the South and Southeast regions, following the resistance guidelines established by the International AIDS Society, United States, primary resistance was rated at 7%, 15 similar to the 7.7% found in Argentina among patients recently infected. 16 In other countries in South America HIV resistance rates were 3.3% in Peru, 17 5.2% in Cuba, 18 and 8.1% in Venezuela. 19 Although only five patients in this study were identified as recently infected by the BED test, three of them had viruses with mutations for resistance, which was found to be statistically significant within the constraints of a small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…3 In another study done with samples collected mostly in the South and Southeast regions, following the resistance guidelines established by the International AIDS Society, United States, primary resistance was rated at 7%, 15 similar to the 7.7% found in Argentina among patients recently infected. 16 In other countries in South America HIV resistance rates were 3.3% in Peru, 17 5.2% in Cuba, 18 and 8.1% in Venezuela. 19 Although only five patients in this study were identified as recently infected by the BED test, three of them had viruses with mutations for resistance, which was found to be statistically significant within the constraints of a small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…36 In most of the studies reviewed, subtype B was the predominant subtype identified, although several other subtypes were present at a prevalence of greater than 10%, including subtype C in Brazil, 25,27,29,30 and recombinant forms in Brazil, 30 as well as in Argentina and Cuba. 34,35 Additionally, one study from Brazil reported non-B, non-C subtypes at a prevalence of 17.0% 29 ; further subtype analysis was not reported.…”
Section: Regional Literature Reviewmentioning
confidence: 99%
“…All studies found by this search were examined; 12 studies of TDR in Latin America and the Caribbean with a sample size of at least 100 adult subjects were identified (Table 3). More than half of the studies were from Brazil [25][26][27][28][29][30] ; the other five countries represented included Colombia, 31 Honduras, 32,33 Cuba, 34 Argentina, 35 and Peru. 36 In most of the studies reviewed, subtype B was the predominant subtype identified, although several other subtypes were present at a prevalence of greater than 10%, including subtype C in Brazil, 25,27,29,30 and recombinant forms in Brazil, 30 as well as in Argentina and Cuba.…”
Section: Regional Literature Reviewmentioning
confidence: 99%
“…The current results were compared with data previously obtained from HIV-1 therapy-experienced patients attending the IPK between May 2003 and September 2003 for viral load testing, irrespective whether or not they were failing. 2 In this previous study, plasma samples from 329 therapy-experienced HIV-1 patients were included of which 175 could be amplified and sequenced. 6 …”
Section: Patient Populationmentioning
confidence: 99%
“…Efforts to provide access to antiretroviral therapy (ART) for HIV patients in need have been accelerated since then and have resulted in a decrease in AIDS mortality rate and incidence of opportunistic infections. 1,2 By the end of 2011, Cuba had 15,824 patients living with HIV of whom 5959 (37.7%) were receiving ART. The most commonly prescribed firstline regimens are zidovudine + lamivudine + nevirapine (∼50%) and stavudine + lamivudine + nevirapine (∼20%).…”
Section: Introductionmentioning
confidence: 99%